PEMIKIRAN TASAWUF HAMKA DAN RELEVANSINYA BAGI KEHIDUPAN MODERN - Salihin Salihin (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2016)
Abstract: One  of the  effects  of modernization on religious  life is a critical attitude  toward religion. Religion, can  only be accepted if; First, in accordance with the teachings sensible advancement of Science. Second, it could  difunctional in answering the challenges of modernity. Hamka  his popular book  Modern Mysticism, which contains about how to build a happy life as desired by Islam. Thought Sufism Hamka not only meant the tarikat region alone but more than that, it is understood that Sufism in general  can be interpreted according to its roots, which the teachings of Islam itself. The methodology used in this study were (1) the type of research; This type of research is the research library (Library Research) (2) of model  approaches; Hermeneutic, use descriptive text or script interpretative against  Sufism thought  Hamka.  While the  main  source is thought  of Sufism Hamka  as outlined  in his books  are: Modern Mysticism, Sufism development of Century Century and Mysticism development and purification. The thesis concludes that the essence of Sufism according to Hamka is aimed at improving the mind and cleanse the mind. Mysticism offered Hamka modern mysticism  or Sufism is positive based on monotheism. Mystical path  through  the ascetic attitude  carried on the official worship, ascetic attitude,  which does not need to be away from normal  life. So therefore, thought  that dynamic Hamka Modern Mysticism extremely relevant  to today’s modern life for a balance between worldly life and ukhrowi.